Cardiopulmonary Resuscitation - Ornato, Joseph P.; Peberdy, Mary Ann.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2005)
Despite more than 50 years of medical progress since the introduction of cardiopulmonary resuscitation (CPR), only 1 out of 5 adults survive in-hospital cardiac arrest, and fewer than 1 in 10 survive out-of-hospital cardiac arrest. In Cardiopulmonary Resuscitation, leading clinicians and scientists-many responsible for the latest international guidelines in resuscitation-comprehensively review the latest therapies and techniques for rescuing persons in cardiac arrest. The authors explore the physiology behind current state-of-the-art clinical resuscitation in depth and translate it into practical bedside recommendations, clinical tips, and expert techniques. Topics of interest include the epidemiology of sudden death; management of ventilation; chest compression technique training; public access defibrillation; drug delivery during CPR; the latest drug therapies; and cardiac arrest in disease, pregnancy, drowning, lightning strike, and trauma. The authors also review the major ongoing research in resuscitation science that will likely affect the next set of international resuscitation guidelines. The design of clinical trials and the ethical issues surrounding resuscitation of both children and adults are discussed extensively. Comprehensive and state-of-the-art, Cardiopulmonary Resuscitation is designed to enhance the ability of resuscitation teams to perform their duties successfully, and save even more lives.
History of the Science of Cardiopulmonary Resuscitation -- Epidemiology of Sudden Death -- Prevention of Sudden Cardiac Death -- Physiology of Ventilation During Cardiac Arrest -- Management of Ventilation During Resuscitation -- Management of Airway Obstruction -- Etiology, Electrophysiology, Myocardial Energy Mechanics, and Treatment of Bradyasystole -- Pulseless Electrical Activity -- Chest Compression Technique -- Alternate Cardiopulmonary Resuscitation Devices and Techniques -- Training Adults to Perform Cardiopulmonary Resuscitation -- External Defibrillation -- Public Access Defibrillation -- Pacing During Cardiac Arrest -- Therapeutic Hypothermia in the Treatment of Cardiac Arrest -- Percutaneous Cardiopulmonary Bypass As an Adjunctive Strategy for Resucitation -- Principles of Drug Delivery During CPR -- Pharmacological Resuscitation Interventions -- Use of Vasopressor Drugs in Cardiac Arrest -- Buffer Therapy -- Anti-Arrhythmic Drugs and Cardiac Resuscitation -- Electrolyte Disturbances and Cardiopulmonary Resuscitation -- Cardiac Arrest in Pregnancy -- Cardiopulmonary Resuscitation Following Drowning -- Cardiopulmonary Resuscitation and Early Management of the Lightning Strike Victim -- Hypothermic Cardiac Arrest -- Cardiopulmonary Resuscitation in Trauma -- Monitoring Techniques During Resuscitation -- Myocardial Dysfunction Postresuscitation -- Postresuscitation Cerebral Dysfunction -- Pediatric Cardiopulmonary Resuscitation -- In-Hospital Resuscitation -- Successful Systems for Out-of-Hospital Resuscitation -- Animal Models of Resuscitation -- Design of Clinical Trials Relating to Medical Emergencies -- Ethics in Resuscitation -- The Future of Cardiopulmonary Resuscitation.
Keywords: Medicine; Cardiology; Medicine & Public Health; Cardiology; Electronic books